The Heart Activities in Some Environmental Temperature on the Rats (Rattus norvegicus) - Amelia Hana; Pudji Astuti; Yuda Heru Fibrianto; Sarmin Sarmin; Claude Mona Airin (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
The aim of this research was to know the heart activity of rats (Rattus norvegicus) at some environmental temperature. Ten rats (Rattus norvegicus), male, 2 months old, the average weight of 200 gr purchased at experiment Animal Care Unit Gadjah Mada University, Yogyakarta. Allf rats were adapted in a cage with food and water ad libitum. Furthermore, each tail rat was measured heart activity is heart rate frequences (beats per minute), mean blood pressure (mmHg), systolic blood pressure (mmHg) and diastolic blood pressure (mmHg) at the environmental temperature of 30o C, 32o C, 34o C, 36o C, 37o C, 38o C, and 40o C measured with a blood pressure cuff BP-98A at coccygea vein for 3 minutes at each temperature. The measurement was repeated 3 times. The data of the heart activities obtained were analyzed by using one way analysis of variance. It was concluded that the environmental temperature of 30o C was optimal to the heart activities of the rats, including heart rate frequences , blood pressure, systolic and diastolic blood pressures.Keywords: heart rate frequences, blood pressure, systolic and diastolic, environment temperature, Rattus norvegicus